Case Report: Severe Persistent Asthma With Acute Exacerbation - Vetho Raweroz; Muhammad Syaifullah; Syafruddin A.R. Lelosutan (International Journal Labs, 2025)
Introduction: Asthma is a chronic inflammatory disease of the airways characterized by airway hyperresponsiveness to various stimuli, leading to recurrent symptoms such as wheezing, shortness of breath, chest tightness, and coughing, especially at night or in the early morning. Case Report: This paper presents an analysis of a 55 year old man who arrived with worsening shortness of breath that had begun five hours before admission. The patient reported being unable to take deep breaths, described a heavy feeling in the chest, and produced audible wheezing. The dyspnea was accompanied by a productive cough with yellowish sputum that became more severe at night. He could not speak fluently-only in short phrases-felt more comfortable sitting upright, and appeared anxious. Spirometry showed an FVC of 48 % predicted and an FEV? of 41 % predicted. Conclusion: Asthma is a chronic inflammatory airway disease with bronchial hyperresponsiveness, causing episodic, variable, and reversible symptoms (wheezing, dyspnea, cough, chest tightness). Diagnosis is primarily established by spirometry. Stepwise therapy (Steps 1–5) is tailored to severity and control to achieve optimal daily symptom control and prevent exacerbations while using the lowest effective dose.